The Superiority of Time-Varying Hedge Ratios in Turkish Futures - Onur Olgun; I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2009)
This paper aims to compare the effectiveness of constant hedge ratio estimates (obtained through OLS and VECM methods) and time-varying hedge ratio estimates (obtained via M-GARCH method) for future contracts of ISE-30 index of TurkDEX. We use portfolio variance reduction as the measure of hedging effectiveness. We find that timevarying hedge ratios outperform the constant ratios for both in-sample and out-of-sample datasets and provide the minimum variance values.
Keywords: G13; G17; 330; Futures Pricing; Hedging; MGARCH; Hedging Effectiveness; Futures; Hedging; ARCH-Modell; Schätzung; Türkei